Clinical study of ritipenem acoxil for surgical field infections - Nohga, Katsuhiko (Japanese Journal of Chemotherapy, 1995)
We administered ritipenem acoxil, an oral penem antibiotic, to 18 patients with surgical field infection (7 with infectious atheroma, 3 with periproctal abscess, 5 with abscess, 2 with wound infection, and 1 with mastitis). Evaluation was possible in 15 patients. The clinical efficacy was excellent in 6 patients and good in 9; the efficacy rate was 100%. Bacteriologically, 20 bacterial strains were isolated from 12 patients. The strain was eradicated in 11 patients but unchanged in 1. None of the patients showed side effects or abnormal laboratory findings associated with administration of this drug.